A nanoarchitectured Na6Fe5(SO4)8/CNTs cathode for building a low-cost 3.6 V sodium-ion full battery with superior sodium storage. Issue 24 (4th June 2019) - Li, Shiyu; Song, Xiaosheng; Kuai, Xiaoxiao; Zhu, Wenchang; Tian, Kai; Li, Xifei; Chen, Mingzhe; Chou, Shulei; Zhao, Jianqing; Gao, Lijun
Abstract : A novel high-voltage cathode material Na6 Fe5 (SO4 )8 (NFS) is successfully prepared for sodium-ion batteries for the first time. It is found that the NFS cathode shows a high working voltage of 3.7 V, together with an attractive energy density approaching 450 W h kg −1 . And, based on an NFS@5%CNTs cathode and hard carbon (HC) anode, a full NFS@5%CNTs//HC cell can deliver an impressive energy density approaching 350 W h kg −1 and excellent cycling stability over 1000 cycles at 2C. Abstract : A high-voltage sodium-ion full battery has been assembled based on Na6 Fe5 (SO4 )8 sulfate structurally integrated with 5 wt% carbon nanotubes (NFS@5%CNTs) acting as the cathode material, with commercialized hard carbon (HC) as the anode material. This full NFS@5%CNTs//HC cell delivers a practical working voltage of 3.6 V and an impressive energy density approaching 350 W h kg −1, and it can retain a specific capacity of 61.8 mA h g −1 after 1000 cycles at 2C. The superior sodium storage performance of this example of a full battery is attributed to the Na6 Fe5 (SO4 )8 cathode material, which is structurally integrated with a conductive CNT component. The CNT additive is tightly implanted and runs through the whole NFS bulk, improving the electrochemical performance of NFS@ x %CNTs cathode materials during the reversible intercalation/deintercalation of sodium ions. The optimized CNT content for NFS@ x %CNTs cathode materials is evaluated to be 5 wt%, resulting in high initial capacities of 110.2 and 86.4 mA h g −1 at 0.1 and 2C, respectively. This work introduces a new derivative of sodium iron sulfates to act as a high-energy cathode material for sodium ion batteries, together with offering an effective CNT-assisted method for enhancing electrochemical performance. A full sodium-ion battery is further developed with a high working voltage and high energy/power densities for practical large-scale applications.